Analisis Tunjangan Kesejahteraan Karyawan Biro Hukum, Organisasi dan Sumber Daya Manusia Pada Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah - Andre Fuad Gunawan; Susan Febriantina; Ervina Maulida (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted at an agency under and responsible to the president of the Government Goods/Services Procurement Policy Agency which provides employee welfare benefits to increase employee morale and loyalty. The purpose of this research was to find out how the agency implements the employee welfare benefit system, to find out the obstacles that occur when distributing employee welfare benefits, and to find out how the agency can resolve these obstacles. According to the views of employees at the Government Goods/Services Procurement Policy Agency, the Bureau of Law, Organization, and Human Resources, employee welfare benefits are very sufficient for the benefits provided, but Employee Benefits only apply to civil servant employees. The Employee Benefit System can be said to be very efficient overall, but some employees experience obstacles when filling in data in the application provided by the Agency, so it is necessary to conduct application training to prevent errors in filling in data in the Agency system